Removal of Various Textile Dyes from Aqueous Solution Using Low Cost Biodegradable Adsorbent - Chowdhury, Miraduzzaman; Hossain, Mohammad Billal (European Scientific Journal, ESJ, 2018)
In textile industry, dyes remove from solution using synthetic materials which is harmful for environment and expensive. In this research work acid treated saw dust(ATSD) used to remove of dyes from aqueous solution. It is environment friendly & cheap. This research work has been carried out using Acid dye,1:2 metal complex dye, Acid-reactive dye, Reactive dye. The objective of work was how many dye separately removes from solution. Acid & 1:2 metal complex dye removed from auxiliary free aqueous solution. In similar dye concentration(gm/l) less ATSD removes acid dye than 1:2 metal complex dye. By Beers-lambert law we explained the deviation of ATSD solution from standard solution of T% & Wavelength curve.